Study on effects and relevant mechanisms of Mudan granules on renal fibrosis in streptozotocin-induced diabetes rats - Mushuang Qi; Xiangka Hu; Wanjun Zhu; Ying Ren; Chunmei Dai (Renal Failure)
Aims The effects and relevant mechanisms of Mudan granules in the renal fibrosis of diabetic rats were explored through in vivo experiments, which provided a scientific basis for expanding their clinical indications.Methods Male SD rats were given a single intraperitoneal injection of STZ (65 mg/kg) to induce diabetes rat models. After treatment with Mudan granules, the general condition of rats was recorded. Blood glucose, blood lipids, and renal function-related indicators were detected, renal tissue morphological changes and fibrosis-related indicators were observed, and the expression of pathway-related proteins were examined.Results The general condition of diabetes rats was improved after the treatment of Mudan granules, the 24-h urinary protein and urinary albumin to creatinine ratio were reduced, and the renal function and lipid results were modified. The tissue damage to the rat kidney has been repaired. Expression of TGF-β1/Smad-related pathway proteins was suppressed in kidney tissues, and the fibrosis factor CO-IV, FN, and LN were reduced in serum.Conclusion Mudan granules may inhibit of TGF-β1/Smad pathway, inhibit the production of ECM, reduce the levels of fibrosis factors CO-IV, FN, and LN, to have a protective effect on kidney in diabetes rats.